Rupture and Resistance in the Poetry of Ogaga Ifowodo: A Postcolonial-Ecocritical Perspective - Oghounu, Ese Christy; Awhefeada, Sunny I.; Ojaruega, Enajite (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025DO - 10.58709/niujhu.v10i1.2112, 2025)
The rupture and the revolutionary movement to resist the exploitation of resources in the Niger Delta based on the obnoxious land tenure system government policies which have led to the degradation of the environment has been explored by writers from the region. The impact of the pollution of the environment on the people includes decrease in economic production as the environment is no longer sustainable. The issue of the loss of land through acquisition by government laws as oil exploration and exploitation sites has also made many communities homeless. The result of this dislocation is protest and resistance of the inhabitants of the region against the oil companies and their government backers. This paper argues that it is the conflict over the control of land between the indigenous people and the government that forms the basis for the ecological degradation of the Niger Delta through irresponsible exploitation of resources.  The study uses the postcolonial-ecocritical theory to assert that the conflict over the ownership and control of the land is the major cause of the degradation in the region. The paper draws illustrations from Ogaga Ifowodo’s The Oil Lamp to prove that through the motifs of paradise, care, seizure, abandonment, exploitation and resistance, the government and the oil companies have turned the once pristine environment of the Niger Delta into an environmental dystopia. The result is resistance by the indigenous people as the land has stopped providing sustenance for them. The use of analepsis, repetition and contrast enable the poet to present a picture of the past, present and the future of the Niger Delta. Keywords: Paradise, Environmental Degradation, Land Seizure, Resistance, Remediation